2015
DOI: 10.1158/1078-0432.ccr-14-0122
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor Heterogeneity in Hepatocellular Carcinoma

Abstract: Purpose: Morphologic intratumor heterogeneity is well known to exist in hepatocellular carcinoma (HCC), but very few systematic analyses of this phenomenon have been performed. The aim of this study was to comprehensively characterize morphologic intratumor heterogeneity in HCC. Also, taken into account were well-known immunohistochemical markers and molecular changes in liver cells that are considered in proposed classifications of liver cell neoplasms or discussed as molecular therapeutic targets.Experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
203
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(217 citation statements)
references
References 42 publications
13
203
0
1
Order By: Relevance
“…Results indicated that heterogeneity of PTPRS expression within individual tumor was 16.7% (2 of 12), similar to the low heterogeneity status of TP53 mutation in HCC. 29 …”
Section: Heterogeneity Of Ptprs Expression In Hccmentioning
confidence: 99%
“…Results indicated that heterogeneity of PTPRS expression within individual tumor was 16.7% (2 of 12), similar to the low heterogeneity status of TP53 mutation in HCC. 29 …”
Section: Heterogeneity Of Ptprs Expression In Hccmentioning
confidence: 99%
“…Further research into tumor biology and biochemistry might provide clues as to why some tumors might respond better than others, and coupled with continued treatment development might make more significant breakthroughs for the treatment of HCC. Intratumoral heterogeneity of HCC has already been described, particularly in large HCCs and is implicated with tumor behavior such as an early tumor recurrence in certain subgroup [15,16]. Improved targeted therapies, combined with effective viral suppression with antiviral therapy, might significantly affect the prognosis of patients with HCC associated with chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that improved patient stratification, as well as combinatorial treatments, might enhance the efficacy of sorafenib. Another challenge for the development of HCC treatment is the substantial degree of tumor heterogeneity, present not only within the tissue, but also on an intra-tumoral level (8).…”
Section: Discussionmentioning
confidence: 99%